Remittances and Income Distribution in Peru - Torres-Zorrilla, Jorge (2008)
Objectives of research were to study the magnitude, dynamics, and impacts associated with remittances to Peru. The remittances grew exponentially in the last decade. The study examines the emigration of Peruvians, compares remittances received by families in Peru with those in countries in Latin America, and presents the income from remittances for families classified by socioeconomic strata. Conclusions are: Peru and Guatemala demonstrate greater growth in remittances during 2000-2005, and Peru shows a high concentration of remittances in the higher quintiles of the socioeconomic strata. This result is unexpected and different from that found in other countries such as Mexico.